2017
DOI: 10.1080/13880209.2017.1314513
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of clove ( Eugenia caryophyllata ) essential oil in human dermal fibroblasts

Abstract: Context: Clove (Eugenia caryophyllata Thunb. [Myrtaceae]) essential oil (CEO) has been shown to possess antimicrobial, antifungal, antiviral, antioxidant, anti-inflammatory and anticancer properties. However, few studies have focused on its topical use.Objective: We investigated the biological activity of a commercially available CEO in a human skin disease model.Materials and methods: We evaluated the effect of CEO on 17 protein biomarkers that play critical roles in inflammation and tissue remodelling in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 15 publications
2
76
0
Order By: Relevance
“…Han and Parker [37] have revealed the antiviral, antimicrobial, antifungal, anticancer, antioxidant, and anti-inflammatory activities of the CEO and its main active constituent eugenol, and they revealed that CEO influenced the cancer biology and cell cycle control. The problems of pathogen resistance, as well as the toxic residues to most of the commercially available antimicrobial drugs severely weaken their effective curative and protective approaches [37][38][39]. Therefore, it is clear that the development of new and effective antimicrobial treatment options is vital for improving disease treatment and control.…”
Section: Biological/biochemical Properties Of S Aromaticummentioning
confidence: 99%
See 2 more Smart Citations
“…Han and Parker [37] have revealed the antiviral, antimicrobial, antifungal, anticancer, antioxidant, and anti-inflammatory activities of the CEO and its main active constituent eugenol, and they revealed that CEO influenced the cancer biology and cell cycle control. The problems of pathogen resistance, as well as the toxic residues to most of the commercially available antimicrobial drugs severely weaken their effective curative and protective approaches [37][38][39]. Therefore, it is clear that the development of new and effective antimicrobial treatment options is vital for improving disease treatment and control.…”
Section: Biological/biochemical Properties Of S Aromaticummentioning
confidence: 99%
“…Pharmacologically, clove oil is used in a wide range as an antiseptic in oral diseases and for the treatment of toothaches, allergy disorders, asthma, acne, scars, and rheumatoid arthritis, and it showed antispasmodic and acaricidal effects toward Dermatophagoides pteronyssinus and Dermatophagoides farina [43,44]. Moreover, the CEO has shown aphrodisiac, antipyretic, appetizer, hypnotic, anxiolytic, antiemetic, analgesic, decongestant, antimicrobial, antiepileptic, myorelaxant, anti-inflammatory, and expectorant properties as well as has a medicinal influence against trophic disorder [37,45]. Notably, tannins, ellagic acid, gallic acid, flavonoids and their glycosides isolated from alcoholic and aqueous clove buds extracts were reported to have antithrombotic, antiprotozoal, hypoglycemic, anti-inflammatory, gastroprotective, and aphrodisiac efficacy [46][47][48][49][50].…”
Section: Biological/biochemical Properties Of S Aromaticummentioning
confidence: 99%
See 1 more Smart Citation
“…Clove, a spice obtained from the dried flower of the tree Syzygium aromaticum L., has been used in traditional medicine for centuries as an antiseptic, analgesic, or in dental care [1]. Nowadays, several studies document a broad range of biological effects of clove including antibacterial [2,3], antifungal [4], antimutagenic [5], antihistaminic [6], antiinflammatory [7], or antioxidant [8]. Moreover, the antiproliferative activity of clove essential oil or eugenol, its main component, has also been described [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The individual essential oils in the EOB that we have studied previously include frankincense and clove oils (Han & Parker, 2017c, 2017d. It was interesting to observe that certain biomarker effects from the individual essential oils were conserved in the blend, while others were lost.…”
Section: Bioactivity Profile Of Eob In Hdf3cgf Systemmentioning
confidence: 96%